Are hypothyroidism and hypogonadism clinically relevant in patients with malignant gliomas? A longitudinal trial in patients with glioma. (January 2019) - Handisurya, Ammon; Rumpold, Tamara; Caucig-Lütgendorf, Carola; Flechl, Birgit; Preusser, Matthias; Ilhan-Mutlu, Aysegül; Dieckmann, Karin; Widhalm, Georg; Grisold, Anna; Wöhrer, Adelheid; Hainfellner, Johannes; Ristl, Robin; et al.
Highlights: Standard postsurgical therapy induces hormonal deficiencies of pituitary and downstream gland. Along with concomitant radiochemotherapy acute "non thyroidal" illness was observed. Secondary hypothyroidism developed during follow up in around 10% of patients. Half of premenopausal women developed early menopause, the percentage of men with lowered testosterone levels appears much lower. Providing adequate hormonal replacement could contribute to decrease fatigue and listlessness. Abstract: Background: So far, the development and course of therapy-induced deficiencies in hypothalamic–pituitary hormones in adult patients with malignant gliomas has not received much attention. However, such deficiencies may impact patient's quality of life substantially. Methods: In this monocentric longitudinal trial, we examined hormonal levels of TSH, T3, T4, fT3, fT4, FSH, LH, testosterone, estradiol and prolactin in patients with malignant high grade gliomas before the start of radiochemotherapy (RCT), at the end of RCT and then every three months for newly diagnosed patients and every six months in patients diagnosed more than two years before study inclusion. Growth hormone was not measured in this trial. Results: 436 patients (198 female, 238 male) with high-grade gliomas, aged 19–83 years (median 50 years), were included in this study. Low levels of thyroid hormones were observed in around 10% of patients within the first six months of follow up and increasingly after 36 months. Half of premenopausal women at study entry developed premature menopause, 35% showed hyperprolactinemia. Low testosterone levels were measured in 37% of men aged less than 50 years and in 35/63 (55%) of men aged 50 years or older. Discussion: The results of this study show that a significant percentage of patients with malignant gliomas develop hormonal deficiencies mandating regular clinical follow up, state of the art counseling and if clinically necessary substitution therapy.